Hematología y Signos Clínicos en Caninos Positivos a Ehrlichiosis en el Centro Veterinario Pomona de la Ciudad de Popayán, Primer Semestre del Año 2022 - Bravo Peña, Diana Marcela; Pérez Guerrero, Falon Cristina (Universidad Antonio Nariño, 2023)
The present study was carried out in the city of Popayán, Cauca; in the Pomona Veterinary Center, strategically selected to evaluate and determine the hematology, physical characteristics and clinical signs of Erlichia spp. in canines by means of the kit test: rapid test for ehrlichiosis of the BIONET laboratory. Sex, age and breed were taken into account in order to detect any predisposition to the disease. Based on a thorough physical examination, hematological testing and the collection of information, we were also able to evaluate the signs or symptoms that were most frequently observed. Over the course of 16 weeks, samples were taken from dogs that visited the clinic for any reason, they came for consultations and agreed with several symptoms in common. We had a positive overall result, since we obtained the number of canines that we needed and participated in our study to carry out the analysis of the final result. We have that within our study there is no marked predominance between sex, but in the males there was a predominance of entire dogs. In terms of lineage, there was no significant difference between mongrels and purebreds. It was observed that more than 50% of the positive dogs were asymptomatic, this being the subclinical stage. As for the most observed symptom, we determined that the disease goes unnoticed due to its subclinical condition or because the owner is not aware or informed of this pathology and the consequences it can have on his pet.